Ownership Concentration and R&D Investments? Variations Brought by Family Control in Taiwan - Irene, Wei Kiong Ting; Kweh, Qian Long; Lo, Huai-Chun (Universiti Malaysia Pahang, 2017)

(untitled)
This study finds that ownership concentration has a positive impact on R&D investments up to a critical point, after which the impact is reversed. Further, the study indicates that family control has a moderating effect on the nonlinear relationship between ownership concentration and R&D investments. More specifically, family-controlled firms are influenced by ownership concentration to a lower extent than non-family controlled firms. Consistent with most prior studies, this study shows that shareholders of a family-controlled firm are involved in the long-term decisions of the firm, and may thus invest in R&D innovation to seek long-term profit maximization in certain situations.